Assessment of the antiproliferative and apoptotic roles of sulfonamide carbonic anhydrase IX inhibitors in HeLa cancer cell line - Koyuncu, Ismail; Gonel, Ataman; Durgun, Mustafa; KOÇYİĞİT, ABDÜRRAHİM; KOÇYİĞİT, ABDÜRRAHİM; Yuksekdag, Ozgur; Supuran, Claudiu T. (My University, 2019)
Carbonic anhydrase IX (CA IX) has recently been validated as an antitumor/antimetastatic drug target. In this study, we examined the underlying molecular mechanisms and the anticancer activity of sulfonamide CA IX inhibitors against cervical cancer cell lines. The effects of several sulfonamides on HeLa, MDA-MB231, HT-29 cancer cell lines, and normal cell lines (HEK-293, PNT-1A) viability were determined. The compounds showed high cytotoxic and apoptotic activities, mainly against HeLa cells overexpressing CA IX. We were also examined for intracellular reactive oxygen species (ROS) production; intra-/extracellular pH changes, for inhibition of cell proliferation, cellular mitochondrial membrane potential change and for the detection of caspase 3, 8, 9, and CA IX protein levels. Of the investigated sulfonamides, one compound was found to possess high cytotoxic and anti-proliferative effects in HeLa cells. The cytotoxic effect occurred via apoptosis, being accompanied by a return of pHe/pHi towards normal values as for other CA IX inhibitors investigated earlier.